TRANSFORMASI BISNIS DIGITAL PADA USAHA SKALA MIKRO DI YOGYAKARTA : ANALISIS SWOT - Maisaroh, Maisaroh; Muslikhah, Rr Siti (Jurnal Riset Entrepreneurship, 2024)
It is a descriptive qualitative research, describing the challenges and opportunities for micro retail businesses to transform their businesses into digital businesses. The samples in this study were 30 micro-scale retail businesses spread across Yogyakarta. The data guidance process was carried out through observation and in-depth interviews conducted with all respondents, from student field practice in Retail and E-Commerce courses through project-based learning methods. By using SWOT analysis, the results of the study show that micro-retail scale businesses in Yogyakarta, their level of readiness to go digital business in terms of product, management organization, knowledge, infrastructure, and market aspects still face challenges that must be faced. Internally, to transform into a digital business, the micro-retail scale in Yogyakarta faces the challenge of increasing its competencies, capabilities, and resources, as well as good market opportunities as initial capital to enter the digital business. Micro retailers must prepare themselves to face these opportunities and challenges in order to be able to enter and win the competition in digital business.